Rotavirus Particles Can Survive Storage in Ambient Tropical Temperatures for More than 2 Months - Fischer, Thea K. (American Society for Microbiology (ASM), 2002)
Typing and in vitro cultivation of rotavirus-positive human stool samples stored unintentionally at ambient tropical temperatures for 2 1/2 months showed that rotavirus is stable and may still be infectious in vitro. This indicates that stool specimen collection for rotavirus studies can be performed in areas and settings where reliable cold storage is not available. The retained infectivity of rotavirus particles underscores the need for safe systems for disposal of feces, in particular in developing countries where rotavirus is a major cause of childhood mortality.